2021
DOI: 10.1186/s12891-021-04538-5
|View full text |Cite
|
Sign up to set email alerts
|

Trunk muscle activation patterns during active hip abduction test during remission from recurrent low back pain: an observational study

Abstract: Background The active hip abduction test (AHAbd) is widely used to evaluate lumbopelvic stability, but the onset of trunk muscle activation during the test in individuals with recurrent low back pain (rLBP) has not been investigated so far. It is important to investigate the pattern of trunk muscle activation during the AHAbd test to provide insight into the interpretation of observation-based assessment results; this may help to create exercise therapy interventions, from a movement control pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…Increased global muscular activity increases spine stress [ 38 ], impairing spine mobility and contributing to shock absorption/damping [ 39 ]. The results of this study support the findings of these previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 34 , 35 , 36 , 37 ]. These inappropriate recruitment patterns may contribute to NSCLBP [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased global muscular activity increases spine stress [ 38 ], impairing spine mobility and contributing to shock absorption/damping [ 39 ]. The results of this study support the findings of these previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 34 , 35 , 36 , 37 ]. These inappropriate recruitment patterns may contribute to NSCLBP [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we showed that the erector spinae muscle activity during the supine bridge exercise using the balance ball, normalized by the floor supine bridge exercise, was significantly greater in the NSCLBP group, and the internal oblique/transversus abdominis muscle activity was significantly lower than in the control group. It has been reported that individuals with LBP show inactivity in the local muscles [ 7 , 12 , 13 , 14 ] and increased activity in the global muscle groups [ 12 , 13 , 14 , 34 , 35 , 36 , 37 ]. The amplitude of transversus abdominis activity was significantly decreased, and the onset timing of transversus abdominis muscle and internal oblique/transversus abdominis muscle was significantly delayed during rapid upper and lower limb movement in individuals with NSCLBP compared to the healthy individuals [ 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicated that in individuals with recurrent LBP, the activation of contralateral erector spinae occurred with a delay compared to those without recurrent LBP during both right and left active hip abduction tests. Additionally, during the left active hip abduction test, the onset of ipsilateral erector spinae activation was present later in individuals with recurrent LBP compared to those without recurrent LBP [ 96 ]. Humphrey et al investigated different sEMG parameters among the healthy, chronic LBP, and past history subjects with LBP.…”
Section: Evaluate Paraspinal Muscles With Semgmentioning
confidence: 99%
“…川崎医療福祉大学 理学療法学科:岡山県倉敷市松島 288 (〒 701-0193) TEL 086-462-11112) 川崎医療福祉大学 作業療法学科 受付日 2022 年 11 月 7 日 受理日 2023 年 1 月 12 日 理学療法科学 38(2) : 96-103, 2023 ■原 著 I.はじめに 本邦において,腰痛の生涯有病率は 83%,その有訴 者率は男性で第 1 位,女性で第 2 位である 1,2) こ と が 報 告 さ れ て い る 18,19) . し た が っ て, は,24 時間以上続く腰痛 が過去 1 年以内に 2 回以上あり,各腰痛発症時の痛みの 強さが Numerical Rating Scale(数値評価スケール)に おいて 2 以上で,各腰痛の発症の間に 30 日以上の無症 状期間がある者としている.そのため本研究の取り込み Sensor M-00-S, Ambu 社 製 ) を 用 い, 皮 膚 処 理 を 行 っ た 後, 先 行 研 究24,25) を参考に貼付した.電極貼付部位は外腹斜筋が 臍外側 15 cm,内腹斜筋が上前腸骨棘の 2 cm 下内側, 腰方形筋が第 12 肋骨と腸骨稜の中間点で脊柱起立筋の 筋腹の外側 4…”
unclassified